(untitled) (Journal of Medical Sciences, 2018)
Bilateral tubal ectopic pregnancy is very rare and usually occurs following ovulation stimulation, with an estimated incidence of 1/2000000 during pregnancy and 1/725-1/1580 ectopic pregnancy. Totally more than 200 cases of bilateral tubal ectopic pregnancies have been reported in the literature. We report 34-year-old primigravida with spontaneous bilateral unruptured tubal ectopic pregnancy. The diagnosis of ectopic pregnancy has been made on clinical suspicion and ultrasonography. The diagnosis of bilateral tubal ectopic pregnancy has been made during surgery and confirmed on histopathological examination. Bilateral tubal ectopic pregnancy is rarely diagnosed preoperative, so both tubes at the time of surgery should be closely examined in order to prevent maternal mortality and morbidity.